Inclusive Growth and Gender Inequality in Asia's Labor Markets - Yana van der Meulen Rodgers; Jr. Zveglich (Asian Development Bank (ADB), 2012)
This study examines gender inequality in labor markets in Asia and the Pacific, with a focus on the structural drivers of women's labor force participation. Demographic survey data indicate that in Asia's lower-income countries, economic necessity is an important push factor behind women's employment. Also, being married and having young children both reduce the likelihood that a woman is employed. In a separate analysis for Taipei,China, this disincentive effect from young children on women's employment has increased over time. These results point to the importance of policies that support women's roles as caregivers while they are employed in market-based activities.
hdl:11540/1263
Keywords: 330; Wirtschaftswachstum; Beschäftigungseffekt; Geschlechterdiskriminierung; Soziale Ungleichheit; Weibliche Arbeitskräfte; Arbeitsmarktdiskriminierung; Asien